2017
DOI: 10.1016/j.jasrep.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

In-situ non-destructive analysis of Etruscan gold jewels with the micro-XRF transportable spectrometer from CNA

Abstract: A B S T R A C TThe study of valuable Cultural Heritage objects frequently requires non-destructive analysis with good sensitivity. Moreover, it is often necessary that the measures are carried out in-situ, in particular when transport of the items from the institutions to the laboratory is not allowed.In this work, the technical specifications of the micro-XRF spectrometer developed at the CNA in Seville is presented and its analytical capabilities are tested by means of the analysis of a set of Etruscan gold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
4
Order By: Relevance
“…The above formulas (1) to (3) indicate that all physical properties of crystalline bodies depend on masses of ions, their charges, and the distance between them. At the same time, according to the periodic law, these characteristics are completely interdependent because the ion mass explains the configuration and number of electron shells, nature, and strength of chemical bonds between ions in the crystal lattice, the distance between ions, and the type of packing.…”
Section: The Results Obtained In the Study Of The Chemical Composimentioning
confidence: 99%
See 1 more Smart Citation
“…The above formulas (1) to (3) indicate that all physical properties of crystalline bodies depend on masses of ions, their charges, and the distance between them. At the same time, according to the periodic law, these characteristics are completely interdependent because the ion mass explains the configuration and number of electron shells, nature, and strength of chemical bonds between ions in the crystal lattice, the distance between ions, and the type of packing.…”
Section: The Results Obtained In the Study Of The Chemical Composimentioning
confidence: 99%
“…Scientists have studied gold jewelry of the VII century B.C. found in Italy [3] and those found in Spain and dated by the VIII-VI centuries B.C. [4].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Dikeranakan metode ini tidak merusak, maka metode ini yang diperguanakan oleh Ortega-Fileu, dkk (2020) untuk menguji kandungan palladium pada perhiasan koleksi Museum Cádiz di Spanyol Selatan (Ortega-Feliu et al, 2020). Selain itu alat uji XRF ini mempunyai tipe portable sehingga dapat dilaksanakan pengujian in-situ artinya contoh uji tidak perlu dibawa ke laboratorium, namun peralatan uji XRF yang dibawa langsung pada benda yang akan diuji, seperti yang dilakukan oleh Scrivano (2017) yang melakukan identifikasi kandungan logam pada emas Estrucan di Museum Arkeologi Nasional Florence (Scrivano et al, 2017).…”
Section: Metode Xrf (X-ray Flourescence)unclassified
“…Separate groups of scientists conducted a study into gold jewelry from VIII-VI centuries BC from treasures found at the territory of Italy [6], Spain [7], Cyprus [8], as well as Egyptian ornaments of XIX-XIII centuries BC [9]. They paid special attention to studying the chemical composition of small elements of gold jewelry and their attachment areas to establish the method for manufacturing these objects.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%